Creativity, self-reflection and subversion: poetry writing for Global Englishes awareness raising. (August 2019) - Rosenhan, Claudia; Galloway, Nicola
Abstract: The current study evaluates the outcomes of a pedagogical task designed to support creative writing pedagogies for second language students and to encourage self-reflection and self-exploration of English. The emancipatory potential and promotion of active learning was seen as conducive to a Global Englishes Language Teaching (GELT) framework in which the course was embedded. Participants were EAP students at a Japanese university, where EAP content utilised Global Englishes for Language Teaching (GELT) subject matter. Poem writing tasks were introduced to develop learners' creative writing skills, individual voice and confidence as multicompetent language users. Analysis of the poems revealed that the task encouraged both self-reflection and creativity and offered opportunities for poetic subversion against the centripetal discourses of English. Through creative play with poetic expression, learners manipulated conventional imagery into original expressions of their own experiences, demonstrating how writing poems had an empowering effect against questions that surround global English language use. Through their poems, learners showed a positive attitude towards English, without giving up their own cultural strengths and individual positions.